2019
DOI: 10.1111/his.13935
|View full text |Cite
|
Sign up to set email alerts
|

Increased tumour angiogenesis in SOX11‐positive mantle cell lymphoma

Abstract: Aims Mantle cell lymphoma (MCL) is a heterogeneous disease with an aggressive behaviour in most cases, which is associated with expression of sex determining region‐Y‐box11 (SOX11). Experimental studies have shown that SOX11 expression is associated with an angiogenic switch characterised by increased expression of angiogenic‐related signatures and vascularisation of murine tumours. However, the relationship between angiogenesis and SOX11 expression in primary tumours is not well understood. Therefore, the aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
(120 reference statements)
1
4
0
Order By: Relevance
“… 30 The relationship between angiogenesis and SOX11 expression has been revealed, and SOX11 was demonstrated to elevate an angiogenic phenotype in primary MCL. 31 Interestingly, our research verified that CCND1 knockdown repressed USP9X overexpression-mediated SOX11 protein level, suggesting that USP9X downregulated CCND1-mediated SOX11 expression in MCL cells. USP9X overexpression could promote WP1130-mediated USP9X, CCND1, and SOX11 protein levels, indicating that USP9X exerts its function by deubiquitinating Cyclin D1 and/or SOX11.…”
Section: Discussionsupporting
confidence: 64%
“… 30 The relationship between angiogenesis and SOX11 expression has been revealed, and SOX11 was demonstrated to elevate an angiogenic phenotype in primary MCL. 31 Interestingly, our research verified that CCND1 knockdown repressed USP9X overexpression-mediated SOX11 protein level, suggesting that USP9X downregulated CCND1-mediated SOX11 expression in MCL cells. USP9X overexpression could promote WP1130-mediated USP9X, CCND1, and SOX11 protein levels, indicating that USP9X exerts its function by deubiquitinating Cyclin D1 and/or SOX11.…”
Section: Discussionsupporting
confidence: 64%
“…Recent studies identified a subgroup of MCL that has a more indolent behavior with a clinical presentation as leukemic disease, exhibiting minimal LN distribution and a frequent splenomegaly. These tumors also overexpress cyclin D1 but lack expression of the sex determining region-Y-box11 (SOX11), a TF specifically expressed in conventional MCL and associated with an aggressive and angiogenic phenotype ( 232 ). These results have been confirmed in MCL patient samples by using immunohistochemistry, demonstrating a correlation between an increased MVD and high levels of SOX11 expression ( 233 ).…”
Section: B Cell Lymphoma-induced Vascular Changes Are Dependent On Thmentioning
confidence: 99%
“…[4][5][6][7] SOX11 contributes to MCL oncogenesis and aggressive behavior through several mechanisms that include blocking the B-cell differentiation program, activation of the B-cell receptor (BCR) signaling pathway, and regulating different interactions between tumor cells and the microenvironment. [8][9][10][11][12][13][14] Some studies have shown that the number of CD4 1 T cells in peripheral blood and tumor infiltrate of MCL positively correlate with low proliferation, indolent disease, and favorable outcome. 15,16 On the other hand, CD40/CD40L interactions seem to promote MCL proliferation and survival.…”
Section: Introductionmentioning
confidence: 99%